Cell recognitive bioadhesive‐based osteogenic barrier coating with localized delivery of bone morphogenetic protein‐2 for accelerated guided bone regeneration - Yun Kee Jo; Bong‐Hyuk Choi; Cong Zhou; Sang Ho Jun; Hyung Joon Cha (Wiley, 2023)
Abstract Titanium mesh (Ti‐mesh) for guided bone regeneration (GBR) approaches has been extensively considered to offer space maintenance in reconstructing the alveolar ridge within bone defects due to its superb mechanical properties and biocompatibility. However, soft tissue invasion across the pores of the Ti‐mesh and intrinsically limited bioactivity of the titanium substrates often hinder satisfactory clinical outcomes in GBR treatments. Here, a cell recognitive osteogenic barrier coating was proposed using a bioengineered mussel adhesive protein (MAP) fused with Alg-Gly-Asp (RGD) peptide to achieve highly accelerated bone regeneration. The fusion bioadhesive MAP‐RGD exhibited outstanding performance as a bioactive physical barrier that enabled effective cell occlusion and a prolonged, localized delivery of bone morphogenetic protein‐2 (BMP‐2). The MAP‐RGD@BMP‐2 coating promoted in vitro cellular behaviors and osteogenic commitments of mesenchymal stem cells (MSCs) via the synergistic crosstalk effects of the RGD peptide and BMP‐2 in a surface‐bound manner. The facile gluing of MAP‐RGD@BMP‐2 onto the Ti‐mesh led to a distinguishable acceleration of the in vivo formation of new bone in terms of quantity and maturity in a rat calvarial defect. Hence, our protein‐based cell recognitive osteogenic barrier coating can be an excellent therapeutic platform to improve the clinical predictability of GBR treatment.